Migration, Health, and Gender and Its Effects on Housing Security of Ghanaian Women - S. Richter; H. Vallianatos; P. Aniteye; K. Ansu-Kyeremeh (SAGE Publishing, 2017)
We explored how migration influences our understanding of health and housing security of women who have or have not migrated to find work in Ghana. This article focuses on housing security. We used a multisite ethnographic research design. The setting was two distinct contexts in Ghana: a rural village and an urban context. We interviewed 44 women. Thematic content analysis was conducted. The main themes that emerged were decisions influencing migration, housing security, and the relationship between housing and health. Women voiced concerns about health related to housing conditions - for example, its effect on upper respiratory infections. We conclude that improving housing and services to the urban poor can have a positive impact on their health. Available, affordable, suitable, and adequate housing has the potential to contribute to economic growth, create more jobs, and improve the well-being of migrant women and, subsequently, their families in Northern Ghana.